(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the multifaceted advantages of Islam in influencing the behavior and development of children. It discusses how Islamic teachings and practices provide moral guidance, discipline, a sense of identity, empathy, cognitive development, conflict resolution skills, respect for diversity, financial literacy, physical well-being, and community engagement. By integrating these dimensions, Islam offers a comprehensive framework for nurturing the holistic well-being of young individuals and equipping them with the values and virtues needed to navigate life’s challenges and contribute positively to society.